Strengthening effects of Al element on strength and impact toughness in titanium alloy - Shixing Huang; Qinyang Zhao; Zhong Yang; Cheng Lin; Yongqing Zhao; Jiashi Yu (Journal of Materials Research and Technology, 2023)
Pure Ti and binary Ti–6Al alloy have been employed as the investigated targets of our research. The strengthening effects of Al element on strength and impact toughness in titanium alloy were systematically investigated. The experimental results indicated that the addition of Al element significantly improved the tensile strength while deteriorating the plasticity and impact toughness. Analysis of deformation mechanisms indicated that addition of Al element strongly inhibited the dislocation movement and deformation twinning in titanium alloy. The theoretical results demonstrated that the dissolution of Al atoms reset the atomic bond configurations and electronic structures of the α-Ti lattice. Therefore, the lattice resistance to dislocation nucleation and dislocation gliding was significantly improved which led to the strong strengthening effect of Al element in α-Ti. The lattice resistance to the shearing atomic motion of deformation twinning was also improved due to the dissolution of Al atoms. Moreover, the strengthening of Al element was revealed at the electronic level by employing the empirical electron theory (EET) of solids and molecules. The strengthening effects of Al element in titanium was also quantitatively evaluated according to the valence electron structure (VES) parameters. A prediction model for the tensile strength of α-type Ti-xAl alloys was proposed based on the quantitative strengthening of Al element. The high accuracy of the prediction model for strength of Ti-xAl alloy was verified by the average error (3.58%) between the computational strength and experimental results.